2019
DOI: 10.3390/app9163409
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Analysis of Large-Scale Rock Slopes Considering the Effect of Microseismic Events

Abstract: To research the macroscopic deformation of rock microseismic damage, a high-precision microseismic monitoring system was established on the left bank slope of the Baihetan hydropower station in Southwestern China. Based on the microseismic monitoring and field deformation data, the seismic source radius was applied to characterize the rock fracture scale. Numerical simulations introduced the rock micro-fracture information into the three-dimensional numerical model of the left bank slope and established the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…If the trend tends to increase, it indicates that stress accumulation occurs in this area, indicating an increase in the rock mass instability and increased risk of rockburst disasters. Zhang et al [57] studied the microseismic evolution characteristics of an underground powerhouse during excavation and found that the apparent stress of the surrounding rock increased significantly before the appearance deformation. Ma et al [58] established an EMS method for rockburst prediction using a combination of seismic energy, seismic moment, and apparent stress.…”
Section: Apparent Stressmentioning
confidence: 99%
“…If the trend tends to increase, it indicates that stress accumulation occurs in this area, indicating an increase in the rock mass instability and increased risk of rockburst disasters. Zhang et al [57] studied the microseismic evolution characteristics of an underground powerhouse during excavation and found that the apparent stress of the surrounding rock increased significantly before the appearance deformation. Ma et al [58] established an EMS method for rockburst prediction using a combination of seismic energy, seismic moment, and apparent stress.…”
Section: Apparent Stressmentioning
confidence: 99%
“…A geomechanical model containing various faults and weak structural planes was established, while a numerical simulation was conducted under normal water load condition through FLAC3D processing to analyze the slope stability [33][34][35][36][37][38]. To research the macroscopic deformation of the left bank slope of the Baihetan Hydropower Station in Southwestern China, the unloading deformation of the left bank abutment rock mass was studied through FLAC numerical calculations [39].…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of the FOS first depends on the limit equilibrium method (LEM), which is based on statistics [6][7][8]. Then, the finite element method (FEM) is used to calculate the FOS to provide detailed stress and strain information [9][10][11][12][13][14][15]. However, both the LEM and FEM can only be used before failure, and cannot show the post-failure behavior of a sliding mass because LEM cannot calculate strain and displacement, and FEM has limitations when it comes to large-deformation analysis.…”
Section: Introductionmentioning
confidence: 99%